2020
DOI: 10.1038/s41598-020-60970-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Ciprofloxacin and Vancomycin on Mechanical Properties of PMMA Cement; a Preliminary Study on Molecular Weight

Abstract: Antibiotic-loaded bone cement (ALBC) is commonly used in joint replacement therapy for prevention and treatment of bone infection and mechanical properties of the cement is still an important issue.The effects of ciprofloxacin and vancomycin was investigated on mechanical characterization of PMMA bone cement. Different properties of cement containing (0, 2.5, 5 and 10% W/W) antibiotics, including compressive and bending properties, microstructural, porosity and density were evaluated. Both antibiotics signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…The use of ALBC is a common practice in arthroplasty; however, the development of antibiotic-resistant bacteria due to the prolonged use of antibiotics makes the treatment of infections even more difficult [132,136]. Additionally, losses in mechanical properties due to the increase in the number of antibiotics that surgeons generally use to reduce the risk of infections rise, generating a premature implant with failures [26,137,138]. Therefore, it is necessary to develop alternatives to antibiotics for the treatment of infections.…”
Section: Antimicrobial Properties In Acrylic Bone Cementsmentioning
confidence: 99%
“…The use of ALBC is a common practice in arthroplasty; however, the development of antibiotic-resistant bacteria due to the prolonged use of antibiotics makes the treatment of infections even more difficult [132,136]. Additionally, losses in mechanical properties due to the increase in the number of antibiotics that surgeons generally use to reduce the risk of infections rise, generating a premature implant with failures [26,137,138]. Therefore, it is necessary to develop alternatives to antibiotics for the treatment of infections.…”
Section: Antimicrobial Properties In Acrylic Bone Cementsmentioning
confidence: 99%
“…Thus, using K IC * = 1.41 MPa.m 0.5 and σ f * = 87.4 MPa in Equations (1) and (2), the r c and d c values for the EMC-MTS and EMC-MS coupled criteria were 0.04 mm and 0.16 mm, respectively. Finally, the fracture loads by the EMC-MTS and EMC-MS criteria can be calculated according to Equations (11) and (12). Equation 11, for the MTS criterion, includes the tangential stress at a critical distance of 0.04 mm from the notch tip (σ θθ ) and for an arbitrary load of 100 N. Analogously, Equation 12, for the MS criterion and for the same arbitrary load of 100 N, includes the mean value of the tangential stress over the critical distance of 0.16 mm from the notch tip (σ θθ mean ).…”
Section: Finite Element Analysesmentioning
confidence: 99%
“…They revealed that by adding nanoparticles to PMMA, the resulting mechanical properties could be improved considerably [10]. Kim et al [11] and Gandomkarzadeh et al [12] studied the fracture properties of bone cement materials by adding vancomycin. They measured the four-point bending strength, compressive strength, and fracture toughness of these materials [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 For this purpose, PMMA cements loaded with various antibiotics such as gentamicin and vancomycin have been developed and some of them have been already commercialized. 13 , 14 In order to extend the antibacterial spectra to resistant bacteria, viruses and so on, non-antibiotic PMMA cements have been recently developed. For example, antibacterial PMMA cements loaded with silver and gold nanoparticles have been proposed.…”
Section: Introductionmentioning
confidence: 99%